Physicochemical, rheological and consumer acceptability of cassava starch salad cream - Adebayo, A.O.; Lateef, S.O.; Elizabeth, A.B. (2010)
Cassava is popularly consumed as a staple in many regions of the developing world. Limitation to utilization of cassava roots by processors is its high perishability and bulkiness. Salad Cream is a ready made creamy-white dressing with a flowing consistency of which modified maize flour serves as the base raw material. At present there is little information on the physical, chemical, pasting and rheological properties of salad cream from cassava starch. This work was aimed to evaluate the physicochemical, rheological and consumer acceptability of cassava starch salad cream from three Nigerian low cyanide cassava varieties (96/01632, 98/0505 and TME419). Commercial salad and cassava starch salad cream were evaluated for physical (colour), chemical (titratable acidity, pH, total solids, protein, sugar, starch, fat, ash, moisture content and dry matter) and rheological (viscosity). Consumer acceptability was evaluated by ten-member panel randomly selected from male and female adults. Lightness (L*) values of cassava starch salad cream from 96/01632 (85.17), 98/0505 (84.21), TME 419 (84.38) and control (77.28), Chroma were 96/01632 (15.77), 98/0505 (16.13), TME 419 (17.59) and control (28.97). Commercial salad cream was significantly higher at p<0.05 in moisture (48.99%), protein (1.61%), sugar (17.59%), titratable acidity (8.63), total solids (61.92%) and ash (2.75%). However, cassava starch salad cream from TME 419 was significantly higher in fat (21.64%). The viscosity of the salad creams was non-Newtonian with cassava starch salad cream from 98/0505 having viscosity (0.43Pa.s) at 500C. Sensory evaluation showed increased preference for cassava starch salad cream. Acceptable and nutritious salad cream can be processed from cassava starch. [Journal of American Science 2010;6(1):65-72]. (ISSN: 1545-1003).